2019
DOI: 10.1002/hyp.13475
|View full text |Cite
|
Sign up to set email alerts
|

Root‐zone moisture replenishment in a native vegetated catchment under Mediterranean climate

Abstract: The root-zone moisture replenishment mechanisms are key unknowns required to understand soil hydrological processes and water sources used by plants. Temporal patterns of root-zone moisture replenishment reflect wetting events that contribute to plant growth and survival and to catchment water yield. In this study, stable oxygen and hydrogen isotopes of twigs and throughfall were continuously monitored to characterize the seasonal variations of the root-zone moisture replenishment in a native vegetated catchme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…Soil samples (50–100 ml) were placed into a zip lock bag, which was then filled with dry, ultra‐high purity nitrogen gas and allowed to equilibrate for 72 h at 23°C and water was sampled and analysed directly from the bag. Cryogenic vacuum distillation was used to extract water from twig samples, following the methods by Xu et al (2019). Briefly, two tubes were attached to a vacuum line, and twig samples were placed into a heated tube (100°C) to release water vapour which transferred to a second tube submerged in liquid nitrogen.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Soil samples (50–100 ml) were placed into a zip lock bag, which was then filled with dry, ultra‐high purity nitrogen gas and allowed to equilibrate for 72 h at 23°C and water was sampled and analysed directly from the bag. Cryogenic vacuum distillation was used to extract water from twig samples, following the methods by Xu et al (2019). Briefly, two tubes were attached to a vacuum line, and twig samples were placed into a heated tube (100°C) to release water vapour which transferred to a second tube submerged in liquid nitrogen.…”
Section: Methodsmentioning
confidence: 99%
“…Cryogenic vacuum distillation was used to extract water from twig samples, following the methods by Xu et al (2019). Briefly, two tubes were attached to a vacuum line, and twig samples were placed into a heated tube (100 C) to release water vapour which transferred to a second tube submerged in liquid nitrogen.…”
Section: Isotope Analysismentioning
confidence: 99%
“…Subsequently, Allen et al (2019) showed that species growing in the same environment used water with distinct seasonal origin. Xu et al, (2019) showed that trees transpire water from first rainfall event that recharged soil water storages during the wet season, and supported transpiration during the dry season. While some synthesis (e.g., J. Evaristo, Jasechko, et al, 2015) and field‐based investigations have found that the use of tightly bound water by trees is widespread across different biomes (G. R. Goldsmith, Muñoz‐Villers, et al, 2012; Hervé‐Fernández et al, 2016), others have not (Geris et al, 2015; Qiu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, Allen et al (2019) showed that species growing in the same environment used water with distinct seasonal origin. Xu et al, (2019) showed that trees transpire water from first rainfall event that recharged soil water storages during the wet season, and supported transpiration during the dry season. While some synthesis (e.g., J.…”
Section: Introductionmentioning
confidence: 99%
“…Given the importance of wet season precipitation to natural ecosystems (Xu et al, 2019) and agriculture in South Australia, it is crucial to know how this teleconnection may impact wet season (winter in South Australia) precipitation processes. Composite analysis is conducted to examine the anomaly of atmospheric circulation over SA winters.…”
Section: Wet-season Rendering Of the Teleconnectionmentioning
confidence: 99%